Implementation of the recruitment and selection paskibraka from the perspective Of pancasila character education - Octavia, Devi; Syarief Nurdin, Encep; Ruyadi, Yadi (Jurnal Pendidikan PKN (Pancasila dan Kewarganegaraan), 2025)
The purpose of this study is to dismantle the implementation of the recruitment and selection policy for the Flag Raising Troop (Paskibra) from the perspective of Pancasila character education. The research method uses a qualitative approach with descriptive analysis. Primary data were obtained from official documentation of the implementation of Paskibra recruitment in 514 Indonesian regencies/cities. Secondary data were obtained from laws and regulations, technical instructions, activity reports, and reputable scientific publications relevant to youth policy, character education and Pancasila ideology. Data analysis was conducted using the Miles & Huberman interactive model consisting of three stages: i) data reduction; ii) data presentation; and iii) conclusions. The validity of the findings used triangulation of sources and techniques, as well as repeated verification to ensure consistency of interpretation. The results of the study reveal a dilemma between maintaining national standards (height, age, and passing the Pancasila Ideology Education test) and equal opportunities across all regions. The main challenges include: i) budget limitations; ii) demographic equality; iii) unequal digital infrastructure; iv) weaknesses of the Paskibraka Transparency Application. The research findings yielded strategies including: i) evaluating discretionary policies; ii) strengthening digital infrastructure; iii) increasing the capacity of regional managers; iv) integrating Pancasila character education from the pre-selection stage in schools. Thus, the Flag Raising Team (Paskibraka) can become a strategic vehicle for training future national leaders with integrity, discipline, and a national spirit